Hubungan Pengetahuan Dan Sikap Remaja Putri Sebelum Dan Setelah Penyuluhan Sadari Di Sman 7 Takalar: The Correlation Knowledge And Attitudes of Young Women Before And After Counseling Breast Self examintion at SMAN 7 Takalar - Nuryana, Riska; Ernawati, Ernawati; Mantasia, Mantasia; Sumarmi, Sumarmi (Jurnal Keperawatan Muhammadiyah, 2024)
Introduction: Adolescence is the start of the process of maturation of the reproductive organs where the increase and changes in hormones occur during this period, one of which is changes in the shape of the breast. Due to the increasing number of cases and lumps that can occur in this organ, an independent detection method is needed to find out lumps in the breast by BSE. Methods: Qualitative research, using a Cross Sectional approach. The population in this study was 133 people and the sample size that met the criteria for being respondents in this study was 81 people. The sampling method used is Non-Propability sampling with purposive technique. Collecting data using a questionnaire, and analyzed using the Chi-Square test. Results: Shows that the knowledge of young women before counseling with less category is 58 people (71.6%), 23 people are enough (28.4%), and none is in Good category (0%). Meanwhile, after counseling, it was found that there were 29 people (35.8%). ) in the positive category and 3 people (3.7%) in the negative category. From the results of the Chi-Square test, it was found that the value of P = 0.00, which means that there is a significant relationship between knowledge and attitudes after counseling on adolescent girls at SMAN 7 Takalar. Discussion: Requires an approach to young people to inform about reproductive health and BSE techniques with the hope that the earlier a tumor or breast cancer is found, the greater the hope for healing. Those who have the results of knowledge produce stimuli so that new knowledge is formed. In addition, there is an internal reaction in the form of individual attitudes towards the results of the knowledge so that sufficient knowledge and good knowledge tend to have a positive attitude.